Small-Scale Industry, Environmental Regulation, and Poverty : The Case of Brazil - Jayaraman, Rajshri; Lanjouw, Peter F. (Washington, DC: World Bank, 2014)
Governments and international development agencies have intensified efforts to promote small-scale enterprises as an engine of pro-poor growth. In Brazil, however, small scale industries may also be responsible for the bulk of air pollution emissions. Although employees of polluting small-scale industries in Brazil are not disproportionately poor, simulations suggest that stringent environmental regulation resulting in widespread closures of pollution-intensive small-scale industries would result in a non-negligible increase in poverty among employees of these firms. The results suggest that the enthusiasm for small-scale enterprises needs to be tempered by awareness of the potential environmental costs imposed by this sector.